KONFLIK ANTARA HUKUM ADAT DAN HUKUM NEGARA : TANTANGAN PENEGAKAN KEADILAN DALAM MASYARAKAT ADAT - Pupu Sriwulan Sumaya (AWATARA Publisher, 2025)
This study aims to analyze the conflict between customary law and state law as well as the challenges of enforcing justice within indigenous communities. A qualitative approach was employed through in-depth interviews, participatory observation, and document analysis. The findings reveal that customary law persists due to its strong social legitimacy, rooted in local values and its effectiveness in maintaining social harmony. Conversely, state law holds formal legitimacy based on statutory regulations, yet often creates tensions when applied without considering customary contexts. The most prominent conflicts occur in land disputes, customary marriages, and resource ownership, reflecting differences in principles and justice orientation. The results indicate the need for context-based integration through hybrid mechanisms that combine customary procedures with state legal principles. Theoretically, this study enriches the legal pluralism literature with empirical evidence of asymmetric legal coexistence. Practically, the findings provide recommendations for policymakers in designing fair and inclusive dispute resolution strategies for indigenous communities.